Endometrial hyperplasia. Experience Hospital Nacional Arzobispo Loayza - Barahona, Sofía (2015)
OBJECTIVES. To determine both endometrial hyperplasia associated risk factors and effective use of diagnostic procedures. DESIGN: Retrospective, clinical study. SETTING: Gynecology Service, Arzobispo Loayza National Hospital, a teaching hospital. PATIENTS: Women with abnormal uterine bleeding and/or thickened endometrium by ultrasound. INTERVENTIONS: Associated risk factors were determined in 196 women –152 premenopausal and 44 postmenopausal–, with histology diagnosis of either endometrial hyperplasia (with or without atypia) or normal endometrium (proliferative or secretory). x2, odds ratios, 95% confidence intervals and logistic regression were used. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were determined. MAIN OUTCOME MEASURES: Endometrial hyperplasia associated risk factors. ReSULTS. In the premenopausal group 34 had normal endometrium, 110 hyperplasia without atypia and 8 hyperplasia with atypia; in postmenopausal women, cases found were 8, 33, and 3, respectively. No association with nulliparity or arterial hypertension was found, but in premenopausal women diastolic blood pressure increased along with lesion severity, without significant difference (normal endometrium 68,8; hyperplasia without atypia 69,4; hyperplasia with atypia 74,3 mmHg). Average basal glycemia levels were higher in hyperplasia with atypia premenopausal women, without significant difference. In postmenopausal women, older age was associated with lesion severity, and average endometrial thickness increased in all pathology types, but without significant differences. Average BMI was as follows: with normal endometrium 26,8, endometrial hyperplasia without atypia 27,9, hyperplasia with atypia 29,1. Abnormal uterine bleeding was more frequent in women with hyperplasia and no atypia (90,9% vs. 77,5%). In the hyperplasia without atypia group hydrosonogram sensitivity was 47,3% and hysteroscopy sensitivity 66,6%, with high NPV (91,2%). For hyperplasia with atypia, hysteroscopy sensitivity was 25%, specificity 60%, PPV 3,1% and NPV 93,8%. Conclusions. No statistical significant associations for endometrial hyperplasia risk factors was found. Hydrosonography and hysteroscopy showed high NPV.